A two-dimensional computational model of a PEMFC with liquid water transport - Siegel, N.P.; Ellis, M.W.; Nelson, D.J.; Von Spakovsky, M.R.
A comprehensive, steady-state, computational model of a proton exchange membrane fuel cell (PEMFC)derived from first principles is presented. The model is two-dimensional and includes the transport of liquid water within the porous electrodes as well as the transport of gaseous species, protons, energy, and water dissolved in the ion conducting polymer. Electrochemical kinetics are modeled with standard rate equations adapted to an agglomerate catalyst layer structure. Some of the physical properties used in constructing the model are determined experimentally for an in-house membrane electrode assembly (MEA)and are presented herein. Experimental esults obtained for the MEA are used to validate the computational model. Modeling results are presented that illustrate the importance of the transport of water within the porous sections of the cell and in the polymer regions of the MEA.
Keywords: COMPUTATIONAL MODEL; PEMFC; PROTON EXCHANGE MEMBRANE; WATER TRANSPORT; AGGLOMERATE